Halal Label as a Moderation of the Influence between Price and Product Quality on Mixue Products Purchasing Decisions in Indonesia - Basuki, Latiffa Queen Azzahra; Maulidizen, Ahmad (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
Since the last five years, the demand for ice cream in Indonesia has increased considerably because ice cream can be a way for people to quench their thirst when the weather is hot. MIXUE is one of the Ice Cream products that has entered the Indonesian market since 2021 and has approximately 317 outlets with consumers who continue to increase. The increase in consumers is because the product tastes good and the price is relatively low, while on the other hand, MIXUE still needs a Halal certificate and label. This research was conducted to analyze the Effect of Price and Product Quality on Purchase Decisions of MIXUE Products with Halal Labels as Moderating Variables. This type of research method uses quantitative methods. This study uses data from 140 respondents who have tried or bought MIXUE products by distributing questionnaires as a Likert scale as primary data. Data processing uses SEM AMOS version 24. The sampling technique is probability sampling, using a simple random sampling technique. The results of this study indicate that: (1) Price has a significant effect on purchasing decisions; (2) Product Quality has no significant effect on Purchasing Decisions; (3) Halal Label has a significant effect on Purchasing Decisions; (4) Halal Label strengthens the relationship between Product Quality and Purchasing Decisions; and (5) Halal Label strengthens the relationship between Price and Purchase Decision.